Les conditions et limites d’un droit à l’altération des données personnelles par les personnes concernées - Claire LEVALLOIS-BARTH; Jonathan KELLER (Tic & Société)
The right of data subjects to self-determination over their personal data, enshrined in the RGPD, is increasingly questioned in a constantly connected society. Contrary to current positive law, the right to alter personal data – the subject of this contribution – would arise prior to processing. In this hypothesis, the data subject could voluntarily alter the quality or truthfulness of his or her personal data in order to conceal its truthfulness. After defining the practical interest and legal foundations of this right, this article tests this hypothetical right in various personal data processing operations carried out either by private operators (for contractual purposes) or by public authorities (for identification or surveillance purposes). Finally, we examine the legal conformity of uses or tools for concealing personal data in this type of context, and conclude with the practical difficulties of implementing this necessary right.